Analisis Komparatif Kesuksesan iPusnas dan Kubuku E-Resources Menggunakan Model DeLone dan McLean - Muh Ahlis Ahwan; Sri Rohyanti Zulaikha; Anis Masruri (Maktabatuna, 2025)
Digital libraries in Indonesia have grown rapidly, yet comparative evaluations of platforms such as iPusnas and Kubuku E-Resources remain limited. This study evaluates the success of both applications using the DeLone and McLean model, which consists of six dimensions: system quality, information quality, service quality, use, user satisfaction, and net benefits. Data were collected through a Likert-scale questionnaire and analyzed descriptively. The results show that Kubuku excels in system aspects and efficiency, with a system quality score of 4.32 and an efficiency/cost-saving benefit score of 4.28, while iPusnas stands out in information personalization (4.35), service responsiveness (4.30), and user satisfaction and loyalty (4.40 and 4.38). Both platforms received positive assessments regarding security and content relevance, each recording values above 4.20. iPusnas and Kubuku are proven to be effective digital library applications, each with distinct strengths, making them representative of high-quality, adaptive, and genuinely beneficial digital libraries.